Knowledge and innovation - Newell, Sue (Henry Stewart Talks, 2011)
Knowledge and Innovation, Changing context of work, The knowledge economy and knowledge-intensive work, Understanding innovation, Traditional linear view to interactive or networked view of innovation, Understanding knowledge, Explicit vs. tacit knowledge, Exploitation and exploration, Characteristics of knowledge as distributed, ambiguous and contested, Managing knowledge for innovation, Knowledge management systems and communities of practice